Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The Impact of Emotional Intelligence on The Professional Judgment of External Auditors in Saudi ArabiaMrs. Atheer Khalaf Owid Al-Juaid, Prof. Fahdah Sultan Al-Sudairi2. The Impact of the New Public Service Model (NPS) on Organizational Efficiency: A Field Study on Saudi Ground Services CompanyMs. Afnan Mohammed Alshehri, Prof. Suzan Mohammed Alqurashi3. Transformational leadership and its role in enhancing digital transformation among Omani teachers in light of Oman Vision 2040Mr. Ali Hamad Salem Al-Buraiki, Dr.Youssef Nait Belaid4. The Role of Artificial Intelligence in Knowledge Management Implementation: An Inductive StudyMr. Arif Khamis Al-Fazari, Prof. Echaoui Abdellah5. Dealing with Future Deals in Light of Bahraini Civil Law: An Analytical StudyCo-Prof. Abdullah Mohammed Almekhlafi6. The Role and Impact of Governance and Evaluation in Enhancing the Quality of Implementation of Construction Projects by Non-Profit Organizations in the Arabian Gulf Region and their representatives between 2018 and 2022Dr. Ezzat Hassane Ali Abdel Sadek, Co-Prof. Ghazi Mustafa Magableh7. The degree of effectiveness of training programs for the employees of the Municipality of Asir RegionMr. Turki Gharman Mohammed Al-Shahri, Mr. Turki Yahya Mohammed Al-Zaidani, Mr. Mohammed Ali Abdullah Al-Shahri
Keywords: Journal of Economic, Administrative and Legal Sciences